Penerapan Kooperatif Numbered Heads Together Meningkatkan Pemahaman Konsep IPA Siswa SMP Negeri Gunungsitoli Utara - Yusmori Isra Putraman Gea; Tektonius Halawa; Jun Mardin Telaumbanua (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2025)
This study investigates the implementation of the Numbered Heads Together cooperative learning model to enhance eighth grade students understanding of science concepts. The research addresses persistent challenges in traditional science instruction where students demonstrate low engagement and weak conceptual mastery. The method employs classroom action research conducted over two cycles with twenty students from SMP Negeri 1 Gunungsitoli Utara. Data collection instruments include observation sheets, learning quality questionnaires, and essay-based concept understanding tests. Results indicate that cycle one achieved a learning quality score of 74.17 percent and a concept understanding average of 81.71. Cycle two showed improvement with learning quality reaching 82.34 percent and concept understanding averaging 85.50. Student active participation increased from 65.31 percent to 81.25 percent across cycles. The findings demonstrate that structured group discussion combined with individual accountability through random numbering significantly improves both conceptual grasp and classroom engagement. Teachers should integrate this model into routine science instruction to foster active learning and deeper comprehension of scientific principles.